A study of trophic structure, physiological condition and mercury biomagnification in swordfish (Xiphias gladius): Evidence of unfavourable conditions for the swordfish population in the Western Mediterranean. (March 2022) - Biton-Porsmoguer, Sebastián; Bănaru, Daniela; Harmelin-Vivien, Mireille; Béarez, Philippe; Bouchoucha, Marc; Marco-Miralles, Françoise; Marquès, Montse; Lloret, Josep
Abstract: Studies integrating trophic ecology, physiological condition and accumulation of heavy metals in top predators, such as swordfish, are needed to better understand the links between them and the risk to humans associated with consumption of these fish. This research focuses on the swordfish of the Catalan Sea and follows a multi method approach that considers their diet, their liver lipid content, and mercury accumulation in their bodies as well as in their prey. The aim is to highlight the links between trophic ecology, physiology (fish condition), and eco-toxicology. Results indicate that poor condition of swordfish based on size and the levels of lipid in the liver, and the high Hg levels accumulated to the trophic web (particularly from cephalopods) may indicate potential unfavourable feeding and reproduction conditions for swordfish in the NW Mediterranean and this warrants further investigation.